Working mother : Challenge from medical and health aspect - Jamani, Nurjasmine Aida (2017)
Malaysia’s force has changed in the last 50 years.The percentage of women working in view of economic needs has steadily been increasing. More women are choosing to continue working while also balancing the traditional parenting responsibility.